Measurement of national-level logistics costs and performance - Karri Rantasila; Lauri Ojala (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2012)
It is necessary to understand logistics performance at the country level in order to better evaluate and target Trade and Transport Facilitation (TTF) policy efforts over time and across countries. Lower costs for logistics reduce the cost of delivering products, thereby encouraging sales, increasing trade, opening new markets and generally encouraging business. Performance evaluation also helps to improve the efficiency of supply chains and the functioning of related infrastructures, services, procedures and regulation. (...)
Keywords: 330